Diagnosis and characterization of solid household waste in the city of Trujillo – Peru, 2019-2020 (SCIÉNDO INGENIUM, 2021)
The purpose of this research was to carry out a characterization and situational diagnosis study of Trujillo solid waste in order to propose, in the future, management solutions based on modern technologies of material and energy recovery. Deductive-inductive and statistical methods were used; the sample chosen was 250 dwellings under a systematic probabilistic sampling and distributed equitably among the 5 territorial zones in which the City is divided; a questionnaire and a data sheet for the identification of critical contamination points, supported by a photographic record, was also applied. The result showed that the total solid waste generation, per capita production, density and humidity percentage were 185,729 t/day, 0.559 kg/hab/day, 291.10 kg/cm3 and 26.64%, respectively. The wastes that are generated in greater proportion are organic with 70.65%, whose biodegradable fraction is 0.82 based on the lignin content of 0.4 volatile solid. In addition, the population lacks ecological culture for proper source segregation, therefore, it is necessary to have an Integrated Solid Waste Management that tends to minimize, where optimization is the key to start with a sustainable habit, framed within a strategy of circular economy.
Keywords: characterization; diagnosis; solid household waste; Trujillo